Heat acclimatization in elite professional Australian football players - Racinais, S.; Buchheit, M.; Bilsborough, J.; Voss, S.; Christian, R.; Hocking, J.; Cordy, J.; Coutts, A. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
This study aimed to determine the benefit of a heat acclimatization camp on physical performance in both neutral and hot environments in 18 elite professional Australian Football (AF) players. Players participated in a two-week pre-season acclimatization camp (environmental temperature 31-33°C, humidity 34-50%). At the beginning and end of the camp, all players performed a heat-response test in a hot environment (24 min walk at 5 km/h + 24 min seated; 44°C, 44% RH) and a YoYo Intermittent Recovery Test level 2 (YoYoIR2) in a neutral environment (22°C). In addition, the total distance and the amount of high speed running (>14.4 km.h-1) were quantified during a standard small-sided game (SSG) in a hot environment (32°C) at the start and the end the camp (average of two SSG at each period). There was an increase in the distance reached during the YoYoIR2 in neutral environment following the camp (+44%, p<0.001). Both the total distance and the amount of high speed running performed by the players during the free-paced SSG in hot environment were also higher at the end than at the beginning of the camp (distance +4.7%, high speed running +10.3%, p<0.045). Results from the heat-response tests showed significant improvement in some (skin temperature -0.5°C, sweat sodium concentration -26%, p<0.01) but not all (core temperature -0.02°C, sweat rate +2%, p>0.65) physiological markers of heat acclimatization over the 2 weeks. Plasma volume calculated by CO rebreathing increased from 4.4 to 4.7 L (p=0.003) and players enhanced their hydration level (specific urine gravity 1.018 vs. 1.013, p=0.003). There were no significant differences in haematocrit levels measured at the end of the heat-response test between at the beginning and end of the camp (42.0% vs. 42.4%, p=0.44). However, the individual changes in haematocrit during the 2 week camp were correlated with the increases in both distance covered (r=0.50) and in the amount of high speed running (r=0.55) during SSG (p<0.05). There was no correlation between the improvement in the YoYoIR2 performance in neutral environment and the increases in physical performance during the SSG in hot environment. In conclusion, the two-week heat acclimatization camp resulted in significant performance enhancement in elite AF players. We observed an increase in the physical capacity tested in neutral environment (YoYoIR2) as well as in the physical performance during competitive situations in hot environment (SSG). However, the correlations analyses suggest that improvement of performance in neutral and hot environments are not directly related and, therefore, may depend on different physiological mechanisms.